Vehicle for modernization in trouble. How the eurozone crisis have changed cohesion policy - Grosse, Tomasz Grzegorz (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2016)
European Union cohesion policy is the main tool of economic and social modernization in less developed countries and regions, notably in Central and Eastern Europe. The article aims to answer the question how the eurozone crisis has affected this policy. In particular, the author intends to study the phenomena observed during the eurozone crisis in (2010–2015) in relation to the field of cohesion policy. Did the policy involve a palpable intensification of intergovern mental management, and did it strengthen the informal role of the largest and richest member states? Did the competences of European Commission grow, albeit without increasing its political autonomy in relation to the EU intergovernmental institutions? Did the crisis reveal the phenomenon of the “two-speed Europe” (a clear division between the eurozone and the rest of the EU) in the sphere of cohesion policy? Or perhaps is there yet another hidden division line within the cohesion policy?

Polityka spójności Unii Europejskiej jest głównym narzędziem modernizacji społecznej i gospodarczej w państwach Europy Środkowej. Dotyczy to zwłaszcza Polski, która otrzymuje największą pomoc finansową z tego instrumentu spośród wszystkich innych państw członkowskich UE. Celem artykułu jest analiza zmian w polityce spójności pod wpływem kryzysu w strefie euro oraz ocena tego, w jaki sposób te zmiany mogą wpłynąć na procesy modernizacyjne w najsłabiej rozwijających się państwach UE, a także szerzej – jak wpłyną na sposób funkcjonowania integracji europejskiej.
Narzędzie modernizacji w kłopotach: jak kryzys w strefie euro zmienił politykę spójności
Keywords: cohesion policy; the eurozone crisis; two-speed Europe; polityka spójności; modernizacja; strefa euro; kryzys; Europa dwóch prędkości